KARAKTERISTIK PENDERITA AIDS DAN INFEKSI OPORTUNISTIK DI RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR PERIODE JULI 2013 SAMPAI JUNI 2014 - Putri Uli Saktina; Bagus Komang Satriyasa (E-Jurnal Medika Udayana, 2017)
AIDS is a set of symptomps due to the decreased of immune system caused by HIV. Opportunistic infections are infections caused by the decrease in the immune system. This study aims to know the description of individual characteristic and opportunistic infections in people with AIDS at Sanglah Hospital Denpasa period July 2013 – June 2014. This study is observational descriptive. The sampel in this study were all patients with AIDS who are hospitalized in Sanglah Hospital period July 2013 – June 2014 that has a complete data. One hundred and seventy nine AIDS patients consist of 121 males (67.6%), mostly between 30-39 years old (39.7%), majority were private employes (43%), Hinduism (74.3%), married (73.7%), and lived in Bali (98.3%). The highest OI type is Candidiasis (28.3%). It is hoped this study ca be useful for management of HIV/AIDS in the future.